Exploring the Inﬂuence of corporate social responsibility on efﬁciency : An extended dynamic data envelopment analysis of the global airline industry - Kao, Fangchen; Ting, Irene Wei Kiong; Chou, Hanchung; Liu, Yisung (MDPI, 2022)
Corporate social responsibility (CSR) has received significant attention from practitioners, encouraging companies to consider it as a business model for their sustainable development. This study examines the effect of CSR on the dynamic efficiency of the global airline industry from 2013 to 2017. The study integrates DuPont and two-stage network data envelopment analyses to evaluate global airline efficiency and its relationship with CSR. Multiple proxies are used to establish a performance evaluation method and analyze the performance of global airlines from the perspectives of their financial structure, production performance and CSR. The study examines the influence of CSR to global airlines’ production efficiency and CSR is measured according to environmental, social and governance activities. The findings are as follows: (1) the profitability of low-cost carriers (LCCs) is superior to that of full-service carriers (FSCs); (2) the energy and wealth-creation efficiencies of LCCs are superior to those of FSCs; (3) FSCs are more committed to CSR activities, and their CSR is positively correlated with overall production efficiency; and (4) environmental and social elements in CSR improve airline efficiency levels. Overall, this study suggests that global airlines should practice CSR to address challenges in the dynamic global airline industry.